Factors Influencing Low Interest in Using Postpartum IUDs in Postpartum Women in South Bolaang Mongondow Regency - Manggopa, Lifta Setiawaty; Zakaria, Fatmah; Melani, Nour Arriza Dwi; Rauf, Efri Leny (An Idea Health Journal, 2026)
Introduction: The family planning program is an initiative aimed at controlling population growth through birth control. Contraception serves as an effective method for planning pregnancies. This quantitative study employed a non-experimental design using an analytical observational method with a cross-sectional approach. The sample consist of 32 respondents selected through accidental sampling. Data were collected using a questionnaire and analyzed with the chi-square test at a significance level of 95% (?=0.05). Chi-square test results showed that the knowledge factor had a p-value of 0.009, indicating a significant relationship with interest in postpartum contraception with use Intrauterine Device (IUD). Husband's support had a p-value of 0.019, counseling or information provided by health workers had a p-value of 0.050, and cultural factors demonstrated a p-value of 0.009, all significantly associated with interest in postpartum contraception with IUD. In conclusion, this study demonstrates a significant relationship between maternal knowledge, husband’s support, information provided by health workers, and cultural influences with the level of interest in IUD use among postnatal mothers